PENGUATAN KEMAMPUAN DAILY COMMUNICATION SISWA BERBAHASA INGGRIS DALAM MENDUKUNG PROGRAM UNGGULAN BAHASA ASING SANTRI DI PONPES BAROKATUL WALIDAIN PIJOT - Rosyidi, Ahmad Zuhri; Paris, Atika Salman; Suryadi, Hendra; Rizki, Muh. Zainal Arifin (LPPM Institut Pendidikan Nusantara Global, 2024)
In the current era, English has become an essential language to master, prompting many people to compete to acquire proficiency. This community service activity aims to support the enhancement of students' English daily communication skills as part of the flagship foreign language program for students at the Barokatul Walidain Pijot Islamic Boarding School. The implementation of this activity began with an introductory socialization session. Subsequently, the community service activities were conducted in the form of training using three methods: lectures, discussions, and practice. Evaluation results from the beginning to the end of the program demonstrated significant improvement. The materials provided in this activity highly motivated participating students to learn English. The students were enthusiastic and thoroughly enjoyed participating in all the activities of the community service program conducted by the team.